A Study on Diagnostic Importance of Fiber Optic Laryngoscopy (FOL) in Patients with Upper Airway Disorders - Mahbub, Shawhely; Al Amin, Ali Zaheer; Biswas, Sudhangshu Shekhar; Jamal, Mohammad Shah (Journal of Bangladesh College of Physicians and Surgeons, 2015)
Background: Upper airway symptoms are quite common. Many of these symptoms underlie serious upper airway pathologies which should be diagnosed at an early stage so that optimum treatment can be given. Often it seems to be difficult to diagnose upper air way pathology by conventional indirect laryngoscopy (I/L), especially when the lesion is at an early stage. In this situation fiber optic laryngoscopy (FOL) is very helpful. Objective: To identify lesions in the larynx in patients with persistent upper airway disorders and to compare the diagnostic yield of FOL over I/L. Method: This was a cross-sectional study conducted partly in department of ENT and Head & neck surgery, BIRDEM General Hospital and partly at the same department of BSMMU during the period of July to December 2012. 100 adult patients were taken having upper airway symptoms. Study subjects were evaluated by history, physical examinations, and ENT examinations. All patients underwent indirect laryngoscopy and FOL. Data were recorded and analyzed. Results: Age of the respondents was between 18-72 years. The mean ± SD was 54 ±11.79 years. Common symptoms among the participants were hoarseness, sore throat, neck swelling, breathless ness, cough, odynophagia, earache etc. On I/L examinations 30% were vocal cord polyps, 14% v. cord edema, 17% v. cord growths, 11% v. cord nodules, 6 % v. cord palsy, 4% ulcerated lesions, 13 % poor vision and 5% were normal. On FOL examinations, 30% were vocal cord polyp, 18% v. cord edema, 21% v. cord growth, 14% v. cord nodule, 8 % v. cord palsy, 5% ulcerated lesion, 2% laryngeal web, 2 % were normal study and there were no poor vision. A comparison was made between the findings of I/L and FOL which showed that FOL is superior to I/L in diagnosing upper airway disorders as evidenced by findings of 2% lesions among 5% patients having normal I/L findings. Chi-square test was done between I/L and FOL findings which was statistically significant; (P value was .002) i.e. FOL procedure is valuable diagnostically in comparison to I/L. Conclusion: In many occasions I/L findings are inconclusive in daily ENT practice. Moreover, in some cases there is poor vision to identify the lesion. Therefore, Routine FOL evaluation is valuable in patients with significant, chronic and progressive upper airway symptoms. It should always be considered in patients with persisting and progressive symptoms even though I/L appeared normal. J Bangladesh Coll Phys Surg 2014; 32: 200-205